CONCUR 2011 - Concurrency Theory 22nd International Conference, CONCUR 2011, Aachen, Germany, September 6-9, 2011. Proceedings - Katoen, Joost-Pieter; König, Barbara (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 22nd International Conference on Concurrency Theory, CONCUR 2011, held in Aachen, Germany, September 5-10, 2011. The 32 revised full papers were carefully reviewed and selected from 94 submissions. The papers are organized in topics such as real-time systems, probabilistic systems, automata, separation logic, ?-calculus, Petri nets, process algebra and modeling, verification, games, and bisimulation.